Sosialisasi Happy Parenting Seni Mengasuh Anak Seputar Ayah Bunda di Desa Ancol Kecamatan Cineam Kabupaten Tasikmalaya - Fani, Andifa Dwi; Salsabila, Salma (Khidmat, 2021)
Parenting is the scientific study of nurturing, educating, and directing children in a positive and appropriate manner. Learning parenting can be challenging and time-consuming for certain individuals. In addition, locating children with distinct personalities is also a challenge. Allah has entrusted children to both parents as a means of mercy for all of humanity and as inheritors of Islamic teachings. Hence, it is crucial for parents to adopt effective parenting practices in order to instill the values of harmonious relationships with both humans and other living beings. During the joyful parenting activities in Ancol village, a significant number of parents exhibit a lack of comprehension of their children's character and struggle to effectively address these issues. In order to address the challenges associated with parenting, particularly in Ancol village as previously said, I propose organising a seminar focused on the skillful upbringing of children, specifically targeting both dads and mothers. This seminar will take place at the Bina Bhakti Ancol posyandu.